New records of Copidognathus (Acari: Halacaridae) from Antalya, Turkey - Furkan Durucan (Persian Journal of Acarology)
The first investigations of the Copidognathus (Trouessart, 1888) halacarid mite fauna of Antalya are reported here. Thirteen species have been found from various macroalgae and sandy sediments. They belonged to the following species: Copidognathus brachystomus Viets, 1940, C. dentatus Viets, 1940, C. gibbus (Trouessart, 1889), C. lamelloides Bartsch, 2000, C. longirostris (Trouessart, 1896), C. loricifer André, 1946, C. magnipalpus (Police, 1909), C. majusculatus (Trouessart, 1894), C. oculatus (Hodge, 1863), C. quadricostatus (Trouessart, 1894), C. remipes (Trouessart, 1894), C. septentrionalis (Halbert, 1915) and C. tabellio (Trouessart, 1894). Of these, C. dentatus, C. gibbus, C. lamelloides, C. longirostris, C. loricifer, C. majusculatus, C. oculatus, C. quadricostatus, C. remipes and C. septentrionalis are new to the Turkish halacarid fauna. Each species is illustrated and briefly described with notes and lastly showed on a Turkish map.